Magnetic Flux Dynamics in HTS Bulks with Levitation Techniques - Kordyuk, O.A.; Nemoshkalenko, V.V.; Plyushchay, O.I.; Viznichenko, R.V. (Успехи физики металлов, 2002)
The discovery of high-temperature superconductors (HTS) has led to understanding that, in order to explain and utilize the phenomenon, completely new physical approaches should be introduced at all scales: microscopic, mesoscopic, macroscopic. Leaving first two scales beyond the scope of the present paper, we focus in the upper limit of the last scale, the study of the magnetic flux dynamics in HTS bulks—the dynamics of the ‘compact vortex structures’. A new direction in the experimental superconducting physics, the investigation of HTS bulks with levitation techniques, which has been elaborated during last years to effectively explore the subject, as well as the new fundamental and applied results obtained there from are overviewed here. Відкриття високотемпературних надпровідників (ВТНП) призвело до розуміння того, що задля пояснення та використання цього явища на всіх рівнях: мікроскопічному, мезоскопічному та макроскопічному, має бути створено принципово нові фізичні підходи. Полишаючи перші два рівні поза увагою даної роботи, ми детально розглядаємо верхню границю останнього — дослідження динаміки магнітного потоку в масивних ВТНП, динаміки «компактових вихорових структур». Дана робота — це огляд нового напрямку експериментальної фізики надпровідників — дослідження масивних ВТНП левітаційними методами — що його було вироблено останнім часом для вивчення зазначеної проблеми, а також тих нових фундаментальних та практичних результатів, що було тут отримано Открытие высокотемпературных сверхпроводников (ВТСП) привело к пониманию того, что для объяснения и использования этого явления необходимо создание принципиально новых физических подходов на всех уровнях: микроскопическом, мезоскопическом, макроскопическом. Оставляя первые два уровня за рамками данной работы, мы сфокусировали внимание на верхнем пределе последнего — исследовании динамики магнитного потока в массивных ВТСП, динамики «компактных вихревых структур». Данная работа — это обзор нового направления экспериментальной физики сверхпроводников, которое было выработано за последние годы, а также тех новых фундаментальных и прикладных результатов, которые были здесь получены.